Tourism development should also pay attention to social components exist in the area, beside the physical and biological condition. Data were collected through literature review and in depth interview. There were 131 respondents consisted of government official (village head), community’s elders, non governmental organization, tourism entrepreneur, and community members which were not involved in tourism activities. Interaction between individuals of the community members in Gunung Sari Villa - Eva Rachmawati; Harini Muntasib; Arzyana Sunkar (Forum Pasca Sarjana, 2011)
Tourism development should also pay attention to social components exist in the area, beside the physical and biological condition.  Data were collected through literature review and in depth interview.  There were 131 respondents consisted of government official (village head), community’s elders, non governmental organization, tourism entrepreneur, and community members which were not involved in tourism activities.  Interaction between individuals of the community members in Gunung Sari Village showed more variations compare to Gunung Bunder 2 Village, due to background variation of community members.  In general, both villages showed positive primary interaction between individuals and groups, since all individuals in a certain group share the same interest and objective.  While interaction between groups were emphasized more on the short term economic interest of nature-based tourism activities rather than the long term nature based tourism development.   Key words: social components, nature-based tourism, Gunung Salak Endah, community